2018
DOI: 10.1093/qjmed/hcy066
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors and characteristics of pediatric stroke: a nationwide population-based study

Abstract: Infants younger than 2 years, boys and children in lower socioeconomic status have a significantly higher risk of stroke. Hemorrhagic stroke has a significantly higher mortality rate than ischemic stroke. More than half of the children with stroke had underlying diseases and the causes of hemorrhagic stroke are significantly different from ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…In very young adults with AIS, aged 18-35 years, dyslipidemia was observed in 37% of them while hypertension was present only in 9% of cases [29]. On the other hand, metabolic disorders, including hyperlipidemia were observed in 2.3% of Taiwanese children with ischemic stroke in a nationwide population study [30]. Interestingly, the study by Bigi et al [31] demonstrated that hyperlipidemia concerned 11 out of 128 children with AIS (aged up to 16 years), as well as 54 young adults (aged 16-45 years), out of 199 analyzed patients and the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…In very young adults with AIS, aged 18-35 years, dyslipidemia was observed in 37% of them while hypertension was present only in 9% of cases [29]. On the other hand, metabolic disorders, including hyperlipidemia were observed in 2.3% of Taiwanese children with ischemic stroke in a nationwide population study [30]. Interestingly, the study by Bigi et al [31] demonstrated that hyperlipidemia concerned 11 out of 128 children with AIS (aged up to 16 years), as well as 54 young adults (aged 16-45 years), out of 199 analyzed patients and the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…As per the Canadian Pediatric Ischemic Stroke Registry data (N = 1,129), a stroke-specific mortality rate of 5% was observed in children with PAIS [ 4 ]. A mortality rate of 10.5% was seen in PIS patients in a nationwide population-based study in Taiwan [ 8 ]. Simonetti et al's study based on the Swiss NeuroPaediatric Stroke Registry (N = 116) found long-term mortality of 14% in children with PAIS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates of 10.5% were seen with PIS in a nationwide population-based study enrolling 685 pediatric stroke cases with 36.1% PIS cases in Taiwan [8]. According to a Kids' Inpatient Database study, PIS has a hospitalization rate of 3.7 per 100,000 children, with the highest rates seen in children under four years of age and those between 15-20 years of age [9].…”
Section: Introductionmentioning
confidence: 99%
“…Haemorrhagic stroke is defined as non-traumatic intracranial haemorrhage which can be subdivided into intracerebral, subarachnoid and intraventricular haemorrhage. The incidence of haemorrhagic stroke lies between 1-3.2 per 100,000 per year and it accounts for approximately 50% of all childhood strokes (2)(3)(4)35,36).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%